A proteção do meio ambiente envolvendo a comunidade de Belém do Pará e os órgãos da segurança pública - TRINDADE, Wildete das Graças Silva da (2019)
The study was based on references and in research on the Amazon region with information collected and compiled on subjects of scientific experiments resources of fauna and flora in the region. Plants, animals and minerals that were extracted in a disorderly way and without control, without regard to the devastation and without care to preserve natural products for future generations. Thus, this work aims through the implementation of projects for implementation of environmental education for the inhabitants of the metropolitan region of Belem, the clarification of issues pertaining to hunting, fishing and sustainable agriculture on a commercial way for the people so they can survive through courses, workshops and lectures in the community. In this regard, we stress the importance of support from public safety agencies and nongovernmental institutions, eradication and alleviation of the problems propitiated by activities that cause serious damage to flora and fauna of the Amazon region, as well as local populations.